Treatment of wealth acquired by unlawful means: an Islamic legal perspective - Ibrahim, Badruddin; Laeba, Muhammad (International Islamic University Malaysia, 2019)
This study examines how Islamic law deals wealth acquired by unlawful means. The main issue is the manner in which to treat all types of unlawful wealth, whether such wealth should be returned to its original owner or given away to charity, the poor and needy, or whether it should even be destroyed. In cases where the person repents, a further issue arises as to whether he is allowed to claim ownership of such wealth or to take possession of some portion of it. The discussion is divided into three parts: part one focuses on the meaning and types of wealth which is acquired through unlawful means; part two explains how Islamic law treats such wealth acquired by unlawful means; and part three extrapolates on the issue of ownership of unlawful wealth after repentance. This study adopts a doctrinal analysis of the Qur’an and Sunnah on issues relating to acquiring wealth through unlawful means. This is followed by a comparative study of the views of Muslim jurists from four well known schools of law as well as those of contemporary Muslim scholars. In addition, reference will also be made to legal opinions (fatawa) from some selected Muslim countries and some renowned contemporary Muslim scholars. It is expected that the study will provide a clear guideline regarding the handling of wealth acquired by unlawful means in Islamic law.